Novel Techniques to Measure the Sensory, Emotional, and Physiological (Biometric) Responses of Consumers toward Foods and Packaging - Torrico, Damir (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book reprinted from articles published in the Special Issue "Novel Techniques to Measure the Sensory, Emotional, and Physiological (Biometric) Responses of Consumers toward Foods and Packaging" of the journal Foods aims to provide a deeper understanding of novel techniques to measure the different sensory, emotional, and physiological responses toward foods. The editor hopes that the findings from this Special Issue can help the broader scientific community to understand the use of novel sensory science techniques that can be used in the evaluation of products.